Cardiac tamponade due to hypothyroidism: a case cluster report. Issue 2 (15th July 2016) - Coetzee, Ankia; Kyriakakis, Charles; Greyling, Chris; Ascott-Evans, BH
Abstract : This study reports on three patients who were seen at Tygerberg Hospital within a short period of six months, with a new diagnosis of biochemically severe primary hypothyroidism. Pericardial effusion was suspected on clinical and X-ray findings and confirmed with echocardiography in all cases. All had evidence of pericardial tamponade based on echocardiographic criteria. Pericardiocentesis was performed on all patients and other causes of pericardial effusions were excluded. Although infrequently described, hypothyroidism needs to be considered in patients presenting with unexplained large pericardial effusions and cardiac tamponade.